2012
DOI: 10.7150/ijbs.8.171
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Caecal MicroRNA Signature Depends on the Presence of the Endogenous Microbiota

Abstract: The intestinal messenger RNA expression signature is affected by the presence and composition of the endogenous microbiota, with effects on host physiology. The intestine is also characterized by a distinctive micronome. However, it is not known if microbes also impact intestinal gene expression epigenetically. We investigated if the murine caecal microRNA expression signature depends on the presence of the microbiota, and the potential implications of this interaction on intestinal barrier function. Three hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 79 publications
(118 reference statements)
3
91
0
2
Order By: Relevance
“…This latter property appears to be based on the capacity of miRs to enter bacteria and directly impact on microbial metabolism. In accordance with the aforementioned work, Singh and colleagues found that caecal miRs profile depends on the presence of the endogenous gut microbiota in mice [81].…”
Section: Gut Microbiota and Mirs Modulation: From Association To Causmentioning
confidence: 49%
“…This latter property appears to be based on the capacity of miRs to enter bacteria and directly impact on microbial metabolism. In accordance with the aforementioned work, Singh and colleagues found that caecal miRs profile depends on the presence of the endogenous gut microbiota in mice [81].…”
Section: Gut Microbiota and Mirs Modulation: From Association To Causmentioning
confidence: 49%
“…The expression of 4.8% of all cecal miRNAs was reported to be differentially expressed when comparing GF and conventionally reared mice (Singh et al, 2012). The potential targets of the differentially expressed miRNAs included genes involved in regulating the intestinal barrier through encoding junctional and mucus layer proteins (Singh et al, 2012). Furthermore, the miRNAs differentially expressed in GF and conventional mice also targeted genes involved in regulating the expression of MHC Class I and II proteins (Singh et al, 2012).…”
Section: Evidence That the Commensal Microbiome Influences Microrna Ementioning
confidence: 96%
“…An interplay between microRNA expression in GIT tissues and the microbiome has been suggested as one possible mechanism to regulate and integrate normal development and function of the mucosal immune system (Masotti, 2012). The expression of 4.8% of all cecal miRNAs was reported to be differentially expressed when comparing GF and conventionally reared mice (Singh et al, 2012). The potential targets of the differentially expressed miRNAs included genes involved in regulating the intestinal barrier through encoding junctional and mucus layer proteins (Singh et al, 2012).…”
Section: Evidence That the Commensal Microbiome Influences Microrna Ementioning
confidence: 98%
See 1 more Smart Citation
“…Given their strength in numbers (~100 trillion) and wellestablished influence on host physiology -particularly by influencing intestinal epithelial cell gene expression -the potential for the gut microbiota to influence miRNA expression in the gut is intuitive. Indeed, recent investigations into this concept have suggested a role for the gut microbiota in eliciting miRNA expression changes throughout the gut [4][5][6][7][8]. A recent paper published in the mBio journal outlined the findings of a study into the miRNA expression response following oral Listeria monocytogenes infection between germfree and conventional mice [9], and deduced that there was differential expression likely mediated through the gut microbiota.…”
mentioning
confidence: 99%